Writing to learn : poetry and literacy across the primary curriculum - Sedgwick, Fred (Routledge/Falmer, 2000)
This book studies the primary curriculum, subject by subject. It aims to help teachers develop Literacy Hour work which is enjoyable, to incorporate themes around personal, social and moral development and to assist in work in ICT.